Analyzing The Effect Of Customer Satisfaction, Service Quality, And Brand Image On Customer Loyalty In E-Commerce Platforms - Sitti Hasbiah (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the effects of customer satisfaction, service quality, and brand image on customer loyalty within e-commerce platforms. by employing a quantitative research approach and surveying active users of major e-commerce platforms, the study finds that customer satisfaction, service quality, and brand image all have significant direct impacts on customer loyalty, with brand image demonstrating the strongest influence. The findings have important implications for e-commerce managers seeking to enhance competitive advantage through loyalty management.